Catastrophes in nature and society : mathematical modeling of complex systems - Khlebopros, R. G. (Rėm Grigorʹevich) (World Scientific, 2007)
Many people are concerned about crises leading to disasters in nature, in social and economic life. The book offers a popular account of the causative mechanisms of critical states and breakdown in a broad range of natural and cultural systems? which obey the same laws? and thus makes the reader aware of the origin of catastrophic events and the ways to avoid and mitigate their negative consequences. The authors apply a single mathematical approach to investigate the revolt of cancer cells that destroy living organisms and population outbreaks that upset natural ecosystems, the balance betwe.